Quantifying the possible role of non-specific forces and cell deformability in the elimination of senescent red blood cells - Bjorn Neu. (2011)
Human erythrocytes have an in vivo live span of about 120 days during which they undergo several physicochemical changes including a greatly enhanced tendency to form aggregates and a decreased deformability. The aging of RBC has been of interest to basic science and clinical investigators for decades but the mechanics leading to phagocytosis and the specific membrane signal(s) allowing the macrophages to distinguish between young and old cells still remain obscure. The central hypothesis of this project is that RBC adhesiveness increases during aging at least partly due to an increase of non specific attractive forces (e.g., increased depletion interaction, decrease of sterical repulsion of adjacent cells). In this project we quantified the impact of certain changes, which occur during RBC aging, on the adhesiveness of RBC to artificial surfaces. This approach is unique in that past works dealing with RBC adhesiveness of senescent RBC have focused on specific (lock and key) forces. It should be noted that the main purpose of this grant was to purchase equipment to supplement the BMRC research grant "Macromolecular depletion as a determinant of red blood cell aggregation and adhesion." The final report of this project can be found in the appendix of this report.